Asymmetric adjustment of control - Victor van Pelt (Contemporary Accounting Research, 2023)
This study examines how principals adjust their control over agents based on their prior controlling experience. According to standard economic theory, principals should be equally willing to decrease their control as they are to increase it. However, I use psychological theory to predict that prior experience with exercising tight control reinforces a principal's belief that agents are self-interested and that they should be controlled. In contrast, I predict that the reinforcement of the belief that agents are socially interested and should not be controlled is weaker for principals who have prior experience with exercising loose control. I test my prediction using an experiment that exposes principals to either an increase or a decrease in the economic costs of control. The results support the predictions by exhibiting an asymmetric adjustment pattern. The data also show theory-consistent conditions under which the asymmetry in principals' control adjustments diminishes. Overall, my study suggests that prolonged experience with exercising high levels of control over agents may cause principals to hold on to their control disproportionally.
Keywords: 650; asymmetry; beliefs; control systems; controls; experiment; stickiness; asymétrie; contrôles; expérience; perceptions; systèmes de contrôle; viscosité